IKHTIAR AKADEMIK MEMBUMIKAN DAN MEMANfAATKAN PRODUK INTELEKTUAL KE RANAH PUBLIC - Mohamad Arif Majid, (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2022)
Since knowledge obtains materials from this life to be examined and developed, it should have further been beneficial to life. In addition, a serious research or study fulfilled by its principles is an internal strategic - positive work, whereas a serious effort to ensure the research results have been truly useful to life is also an external strategic – positive one. Departing from this thought, the author proposes a concept of Bedah jurnal (Journal review) as a strategic positive effort to guarantee, as an external work, the life has received the advantages of the research findings. Thus, Bedah jurnal is an external effort, which technically is similar to Bedah buku (book review), done by inviting the selected writers of the published articles at each issue and attended by the stakeholders. At the final part of this paper, the author explains how this Bedah jurnal is believed to give great advantages to the lectures or writers, institutions or campuses, and to the nation and society.